Pengabdian Masyarakat Pemberdayaan Masyakarat dalam Meningkatkan Nafsu Makan Melalui Pijat Tui Na di RW II Desa Kalirejo Kecamatan Ungaran Kabupaten Semarang - Bq. Yulia Sri A; Munasifah; P. R, Arina Manasika; Rahmadhani, Tesa Dwiputri; Atika Rizki Suryani; Andy Ulmi Aprilani; Agan Sridewi; Moneca Diah Listiyaningsih (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2023)
Community is a collection of people who have at least one characteristic in common such as geography, occupation, ethnicity, interests and others. Alternative complementary medicine is non-conventional treatment aimed at improving public health status including promotive, curative, preventive and rehabilitative efforts. Public health can be improved by providing information about  health  through  counseling  activities.  Providing information during pregnancy, childbirth, postpartum can increase the mother's knowledge so that it influences her behavior  in  the  care  of  pregnancy,  childbirth  and postpartum. In community service activities there are health problems related to toddlers. Toddlers are children under the age of 5 years who have the characteristics of being 1-3 years old and preschool children (3-5 years).. During this period children are also vulnerable to high morbidity because are more likely to get sick, which can cause a decrease in appetite. Toddlers need three things for optimal growth and development, namely nutrition (nurture and environment), affection (affection) and sharpness (stimulation). The eating habits of 1 year old babies are mostly passive, usually this problem appears at the age of 1 year. Loss of appetite is often caused by subsequent eating disorders. the occurrence of eating difficulties. This is because at that age children can choose the foods they like and only the foods they like. Difficulty eating in children has a negative impact on children. This effect not only affects health, but also affects daily activities as well as children's growth and development. The consequences of eating difficulties include malnutrition. Efforts to overcome eating difficulties in toddlers are carried out using non-pharmacological methods through tui na massage. Implementation          is          by        counseling       about complementary therapies in midwifery services, namely prenatal yoga, breast care, oxytocin massage. This activity involved health workers from the Jenar Village Midwife and the community, especially pregnant  women  and postpartum women. This community was carried out in Jenar Village, Jenar District, Sragen Regency. implementation time in November 2022. Participants in this Community activity were catin women with a total of 1 person, pregnant women with a total of 16 people, toddlers with a total of 98 people and postpartum mothers with a total of 1 person. The activity is carried out in stages (1) providing an explanation of the purpose of the activity; (2) provide education about complementary therapies and their benefits for maternal health (3) train pregnant women and postpartum mothers to do prenatal yoga, and breast care, oxytocin massage (4) provide explanations of knowledge about pregnancy planning to prospective brides (5) provide explanations and education about stimulation of growth and development in toddlers. The activity showed that there was an increase in the knowledge of the bride and groom regarding pregnancy planning, mothers of toddlers regarding stimulation of child growth and development, pregnant women and postpartum mothers about complementary therapy, after counseling and education for prospective brides and toddlers, then prenatal yoga, breast care and oxytocin massage for pregnant women and postpartum women who feel that there are benefits for physical and psychological health. After carrying out this community activity, there was an increase in public knowledge, especially prospective brides, mothers under five, pregnant women, postpartum mothers about counseling on pregnancy planning, stimulation of growth and development in children, classes for pregnant women, prenatal yoga, counseling for postpartum mothers, breast care, oxytocin massage, and after counseling the bride and groom, mothers of toddlers, pregnant women, postpartum mothers want to take part in this community activity.   Abstrak Komunitas adalah kelompok sosial yang tinggal dalam suatu tempat, saling berinteraksi satu sama lain, saling mengenal serta mempunyai minat dan interest yang sama. Komunitas adalah kelompok dari masyarakat yang tinggal di suatu lokasi yang sama dengan dibawah pemerintahan yang sama, area atau lokasi yang sama dimana mereka tinggal, kelompok sosial yang mempunyai interest yang sama. Dalam kegiatan pengabdian masyarakat terdapat permaslahan kesehatan terkait dengan balita, Balita merupakan anak di bawah usia 5 tahun yang memiliki ciri-ciri berusia 1-3 tahun dan anak prasekolah (3-5 tahun).. Pada masa tersebut anak juga rentan terjadi morbiditas tinggi karena lebih cenderung sakit, yang dapat menyebabkan penurunan nafsu makan. Balita membutuhkan tiga hal untuk tumbuh kembang yang optimal, yaitu nutrisi (pengasuhan dan lingkungan), kasih sayang (kasih sayang) dan ketajaman (stimulasi) Kebiasaan makan bayi usia 1 tahun kebanyakan pasif, biasanya masalah ini muncul pada usia 1 tahun. Kehilangan nafsu makan sering kali disebabkan oleh gangguan makan selanjutnya. terjadinya masalah kesulitan makan. Hal ini disebabkan pada usia tersebut anak sudah bisa memilih -milih makanan yang disukainya dan hanya makanan yang disukai. Kesulitan makan anak berdampak negatif pada anak. Efek ini tidak hanya mempengaruhi kesehatan, tetapi juga mempengaruhi aktivitas sehari-hari serta pertumbuhan dan perkembangan anak. Konsekuensi dari kesulitan makan antara lain malnutrisi, upaya dalam mengatasi kesulitan makan pada balita dilakukan dengan cara non farmakologi melalui pijat tui na. Pelaksanaan kegiatan pengabdian masyarakat  dengan memberikan penyuluhan tentang terapi komplementer Pijat Tui na pada balita  Kegiatan ini melibatkan tenaga kesehatan Bidan Desa Kalirejo dan masyarakat khususnya Ibu yang memiliki balita,  Komunitas ini dilakukan di Desa Kalirejo Kecamatan Ungaran Timur Kabupaten Semarang. waktu pelaksanaan pada bulan Desember tahun 2023. Peserta kegiatan Komunitas ini adalah ibu hamil jumlah 1 orang, balita dengan jumlah 17 orang. Kegiatan dilakukan dengan tahapan (1) memberikan penjelasan tentang tujuan kegiatan; (2) memberikan edukasi tentang terapi komplementer dan  manfaatnya bagi Kesehatan ibu dan Balita (3) melatih balita melakukan pijat Tui na,(4) memberi penjelasan pengetahuan tentang pijat tui na dalam meningkatkan nafsu makan pada balita, Kegiatan menunjukkan ada peningkatan pengetahuan setelah diberikan  pendidikan  kesehatan       pada ibu hamil dalam mengurangi nyeri pungung dan balita tentang manfaat pijat Tui na untuk meningkatkan nafsu makan, setelah dilakukan penyuluhan dan edukasi untuk ibu hamil dan balita merasakan ada manfaat bagi kesehatan fisik dan psikis. Setelah dilakukan kegiatan komunitas ini terdapat peningkatan pengetahuan masyarakat khususnya ibu hamil dan balita tentang penyuluhan  tentang cara mengurangi nyeri punggung  dan pijat Tui na dalam meningkatkan nafsu makan kemudian ibu dan balita mau mengikuti kegiatan komunitas ini